BMP Signals Promote Proepicardial Protrusion Necessary for Recruitment of Coronary Vessel and Epicardial Progenitors to the Heart - Ishii, Yasuo (2010)
The coronary vessels and epicardium arise from an extracardiac rudiment called the proepicardium. Failed fusion of the proepicardium to the heart results in severe coronary and heart defects. However, it is unknown how the proepicardium protrudes toward and attaches to the looping heart tube. Here we show that ectopic expression of BMP ligands in the embryonic myocardium can cause proepicardial cells to target aberrant regions of the heart. Additionally, misexpression of a BMP antagonist, Noggin, suppresses proepicardium protrusion and contact with the heart. Finally, proepicardium explant preferentially expands toward a co-cultured heart segment. This preference can be mimicked by BMP2/4 and suppressed by Noggin. These results support a model in which myocardium-derived BMP signals regulate the entry of coronary progenitors to the specific site of the heart by directing their morphogenetic movement.